The effect of avocado butter to characteristics of emullient W/O cream - Teti Indrawati; Herlina Yuanita Sari (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2010)
Avocado butter is an unsafonifiable fraction of avocado oil that contains of 25-30 % fitosterol as anti-aging agent. In this research, the influence of 6 variation avocado butter between 1–11 % to o/w cream characteristics has been researched. O/W cream has been made by meltingand mixing methods at 700C, and than cream product was evaluated. The result showed that o/w cream characteristics were progressively influenced by amount of avocado butter. In using avocado butter between 1–7 % in creams, the value of pH, viscosity, and particle size in product creams progressively go down, but theirs spread-abilities progressively go up. On the contrary cream characteristics that usage 9% of avocado butter, the value of viscosity and particle size began to go up while pH, but spread-abilities go down.Key words :avocado butter, O/W cream, cream characteristic, stability